Plasma Alkylresorcinol Metabolite, a Biomarker for Whole-Grain Intake, Is Inversely Associated with Risk of Nonalcoholic Fatty Liver Disease in a Case-Control Study of Chinese Adults. Issue 4 (29th January 2022) - Sun, Taoping; Deng, Yao; Geng, Xuyang; Fang, Qin; Li, Xiaoqin; Chen, Liangkai; Zhan, Meixiao; Li, Deyun; Zhu, Kejing; Li, Huawen; Liu, Liegang
ABSTRACT: Background: Epidemiologic studies consistently find associations between whole-grain intake and reduced risk of obesity and related metabolic diseases, yet data on the potential of whole grains to prevent fatty liver diseases are scarce. Objectives: To examine whether plasma 3-(3, 5-dihydroxyphenyl)-1-propanoic acid (DHPPA), a biomarker of whole-grain wheat and rye intake, is associated with nonalcoholic fatty liver disease (NAFLD). Methods: This case-control study of Chinese adults enrolled 940 NAFLD cases and 940 age- and sex-matched non-NAFLD controls (mean age: 55.2 y; 65% males). NAFLD diagnosis was defined as individuals whose hepatic ultrasound disclosed hepatic steatosis at any stage, after the exclusion of alcohol abuse and other liver diseases. Fasting plasma DHPPA concentration was measured by LC-MS/MS. Multivariate adjusted ORs and 95% CIs were estimated to assess the association between plasma DHPPA and NAFLD using conditional logistic regression. Results: Plasma concentration of DHPPA was significantly lower in patients with NAFLD compared with controls (median: 9.86 nmol/L compared with 10.9 nmol/L, P  = 0.002). In multivariable logistic regression models, the ORs (95% CIs) for NAFLD across increasing tertiles of plasma DHPPA were 1 (reference), 0.76 (0.54, 1.05), and 0.65 (0.45, 0.93), respectively ( P -trend = 0.026). In addition, the inverse associations persisted in subgroups stratified by sex, age, BMI, abdominal adiposity, smoking status, physical activity, diabetes, hypertension, and hyperlipidemia. Conclusions: These results indicate that increased plasma DHPPA concentration is associated with lower risk of NAFLD in Chinese adults, independently of well-known risk factors. Our finding provides evidence to support health benefits of whole-grain consumption on NAFLD. This trial was registered at clinicaltrials.gov as NCT03845868.